Dysregulation of Parvalbumin Expression in the Cntnap2−/− Mouse Model of Autism Spectrum Disorder - Lauber, Emanuel; Filice, Federica; Schwaller, Beat (Frontiers in Molecular Neuroscience, 2018)
Due to the complex and heterogeneous etiology of autism spectrum disorder (ASD), identification of convergent pathways and/or common molecular endpoints in the pathophysiological processes of ASD development are highly needed in order to facilitate treatment approaches targeted at the core symptoms. We recently reported on decreased expression of the Ca2+-binding protein parvalbumin (PV) in three well-characterized ASD mouse models, Shank1-/-, Shank3B-/- and in utero VPA-exposed mice. Moreover, PV-deficient mice (PV+/- and PV-/-) were found to show behavioral impairments and neuroanatomical changes closely resembling those frequently found in human ASD individuals. Here, we combined a stereology-based approach with molecular biology methods to assess changes in the subpopulation of PV-expressing (Pvalb) interneurons in the recently characterized contactin-associated protein-like 2 (Cntnap2-/-) knockout mouse model of ASD. The CNTNAP2 gene codes for a synaptic cell adhesion molecule involved in neurodevelopmental processes; mutations affecting the human CNTNAP2 locus are associated with human ASD core symptoms, in particular speech and language problems. We demonstrate that in Cntnap2-/- mice, no loss of Pvalb neurons is evident in ASD-associated brain regions including the striatum, somatosensory cortex (SSC) and medial prefrontal cortex (mPFC), shown by the unaltered number of Pvalb neurons ensheathed by VVA-positive perineuronal nets. However, the number of PV-immunoreactive (PV+) neurons and PV protein levels were decreased selectively in the striatum of Cntnap2-/- mice. Transcript levels of Hcn4, coding for the hyperpolarization-activated cyclic nucleotide-gated channel 4 (Hcn4), were down-regulated in striatal extracts from Cntnap2-/- mice. Previously shown in ES-derived human neurons with conditional SHANK3 deletions, a gene representing another validated ASD risk gene, Hcn4 (and Hcn3) levels were also decreased. Moreover, both Cntnap2-/- and Shank3B-/- mice are characterized by striatal PV down-regulation. This hints towards yet another point of (molecular) convergence caused by the absence of Cntnap2 and Shank3. Considering that Cntnap2 shows high expression levels in the striatum during human and mouse embryonic development and that the cortico-striato-thalamic circuitry is important for speech and language development, alterations in striatal PV expression and associated (homeostatic) adaptations are likely to play an important role in Cntnap2-/- mice and, assumingly, in human ASD patients with known Cntnap2 mutations.